Analisis Perhitungan Jasa Kontruksi Berdasarkan PPh Final (4 Ayat 2) dan PPh Pasal 23 pada CV. Pratama Karya Mandiri - Rahmat Syaifuddin; Lis Setyowati (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
. The purpose of this study is to determine the calculation of income tax (PPh 4 paragraph 2 and PPh Article 23) on construction services at CV. Pratama Karya Mandiri. Data collection techniques are obtained through a descriptive approach which aims to find out the problem being solved so that an overview of the problem being studied is obtained. Using data in the form of gross income recapitulation, the type of research used is qualitative research. This qualitative research is conducted on scientific objects that develop, and are not manipulated by researchers and the dynamics of these objects are not affected by the presence of researchers.The results of this study indicate that the taxation calculations carried out by CV. Pratama Karya Mandiri related to Income Tax on construction services is in accordance with the latest tax regulations, especially in terms of tax rates.